Determination of caesarean section rate and its trend analysis in a tertiary care tribal preponderant state using Robson’s classification - Bharti, Atima; Hansda, Rani; Prakash, Ayushi; Madhu; Sardar, Arpana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: There are certain conditions during delivery where vaginal delivery becomes unsafe. To overcome this situation, caesarean section (CS) is necessary for the safety of the mother and baby. The incidence of CS is rising to improve the outcome of mother and baby; it is a life-saving surgical tool in the process of delivering the baby. Efforts are being made to decrease the rate of CS without adversely affecting the outcome of the mother and baby. Robson’s classification for the indication of CS is an excellent method to audit for the indication of the surgery. However, this classification does not include some important indications like placenta previa, which is on the rise in the present day. Methods: This study was a hospital-based prospective observational study that enrolled 2066 pregnant females, conducted from October 2023 to September 2024 in a tertiary health centre. Results: Delivery by vaginal route and CS was 4561 during one year period, 2066 women was delivered by CS accounting an incidence of 45.29%. The majority of patients were in the age group of 20-30 years (75.9%), 82.1% were from rural areas, and the majority of women were unbooked (70%), 57.4% were multiparous, and 51.3% of the patients belonged to the tribal community. Conclusions: Standardisation of CS indication parameters, regular CS audits, and application of Robson classification for every woman undergoing a CS will be helpful to keep a check on rising CS rates.